The Polish Marco Polo – Explorer of Zhōngguó: The Contribution of Michael Boym (c. 1612-1659) to the European Perception of the Geography, Linguistics, History, Politics, Nature and Medicine of China (Politeja, 2025)
The failed diplomatic mission of Michael Boym is still a little-known episode. Nevertheless, Boym’s legacy goes beyond his missionary and political activities. This tireless researcher left us a collection of invaluable treatises that introduced Europeans to various phenomena of imperial China that were unknown at the time. Europe owes Boym a great deal of reliable knowledge about Chinese geography, history, philosophy, medicine, nature, local folklore and even astronomy. Boym’s rich scholarly output in these numerous subject areas, which was created during his numerous travels, is astonishing.